Becoming bicultural : risk, resilience, and Latino youth - Smokowski, Paul R. (Paul Richard) (New York University Press, 2011)
Although the United States has always been a nation of immigrants, the recent demographic shifts resulting in burgeoning young Latino and Asian populations have literally changed the face of the nation. This wave of massive immigration has led to a nationwide struggle with the need to become bicultural, a difficult and sometimes painful process of navigating between ethnic cultures. While some Latino adolescents become alienated and turn to antisocial behavior and substance use, others go on to excel in school, have successful careers, and build healthy families.